FACTORS ASSOCIATED WITH INCIDENCE OF HYPERTENSION IN THE PATEK HEALTH CENTER AREA ACEH JAYA DISTRICT - Najikhah, Nur; Maulidiana, Putri (Transpublika Publisher, 2023)
Hypertension is a disease that is still the biggest problem in the world. Hypertension can cause complications for several other diseases, such as heart disease, stroke and kidney disease. According to WHO, the diagnosis of hypertension in adults is determined by at least two visits where it is higher or at 140/90 mmHg. The purpose of this study was to determine the factors that influence hypertension. Quantitative research with analytic descriptive design using a cross sectional study approach. The research sample of clients with hypertension is 30 respondents. Based on the results of the study, the factors that cause hypertension can be classified into uncontrollable hypertension factors such as family history, gender, and age and controllable factors such as food consumption patterns, smoking behavior, obesity, and lack of physical activity. In the study it was found that 1) smoking habits by 50% which indicates that there is a possibility of hypertension can be interpreted as smoking habits as one of the triggers for hypertension. 2) Obesity is 53.3%, in this study the level of obesity does not affect the relationship to hypertension, but obesity is a factor in hypertension. 3) The stress level is 46.7% and 53.3% is not, so it does not affect the incidence of hypertension but stress is one of the factors causing hypertension. 4) In physical activity it shows a value of 53.3 which does not carry out physical activity so that this affects the incidence of hypertension.